2005
DOI: 10.1097/00008469-200506000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of aflatoxin B1-induced genotoxicity and hepatic oxidative damage in rats by kolaviron, a natural biflavonoid of Garcinia kola seeds

Abstract: The chemopreventive effects of kolaviron, a natural antioxidant bioflavonoid from the seeds of Garcinia kola, on aflatoxin B1 (AFB1)-induced genotoxicity and hepatic oxidative damage was investigated in rats. Kolaviron administered orally at a dose of 200 mg/kg once a day for the first 2 weeks and then 100 mg/kg twice a day for the last 4 weeks of AFB1 (2 mg/kg, single dose, intraperitoneal) treatment reduced the AFB1-increased activities of aspartate amino transferase (AST), alanine amino transferase (ALT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(89 citation statements)
references
References 41 publications
2
86
1
Order By: Relevance
“…The mechanism of striatal cell death after systemic administration of 3-Nitropropionic acid is not well understood, although several factors may contribute to selective vulnerability of medium-sized spiny striatal neurons. Decortication, which removes putative gluatmatergic inputs to the caudate putamen, can protect against 3-Nitropropionic acid toxicity in the caudate putamen [4,[19][20] , and N-Methy-DAspartate receptors are up-regulated in both cortex and caudate putamen following 3-Nitropropionic acid injection [4,[21][22][23] . These are both lines of evidence for a secondary excitotoxic mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mechanism of striatal cell death after systemic administration of 3-Nitropropionic acid is not well understood, although several factors may contribute to selective vulnerability of medium-sized spiny striatal neurons. Decortication, which removes putative gluatmatergic inputs to the caudate putamen, can protect against 3-Nitropropionic acid toxicity in the caudate putamen [4,[19][20] , and N-Methy-DAspartate receptors are up-regulated in both cortex and caudate putamen following 3-Nitropropionic acid injection [4,[21][22][23] . These are both lines of evidence for a secondary excitotoxic mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The mice in the treatment groups received 20 mg/kg body weight of 3-Nitropropioic acid intraperitoneally. The control group received an equivalent volume of distilled water intraperitoneally.…”
Section: Drug Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…It is often consumed among various cultures of Nigeria especially for its stimulatory effects (Atawodi et al., 1995). Although previous studies have reported various extracts and fractions of GK seed for their therapeutic uses in treating throat infections, bronchitis, cough, hepatitis, liver disorders (Farombi, Adepoju, Ola‐Davies, & Emerole, 2005), the fact that consumption of whole seeds especially for long time produce stimulant‐like effect could induce some toxicological effects which is worth investigating. This study therefore investigates the effects of GK seed on survival, locomotion, and oxidative stress markers in D. melanogaster .…”
Section: Introductionmentioning
confidence: 99%